Accounting for variation in and overuse of antibiotics among humans. (6th January 2021) - Blaser, Martin J.; Melby, Melissa K.; Lock, Margaret; Nichter, Mark
Abstract: Worldwide, antibiotic use is increasing, but many infections against which antibiotics are applied are not even caused by bacteria. Over‐the‐counter and internet sales preclude physician oversight. Regional differences, between and within countries highlight many potential factors influencing antibiotic use. Taking a systems perspective that considers pharmaceutical commodity chains, we examine antibiotic overuse from the vantage point of both sides of the therapeutic relationship. We examine patterns and expectations of practitioners and patients, institutional policies and pressures, the business strategies of pharmaceutical companies and distributors, and cultural drivers of variation. Solutions to improve antibiotic stewardship include practitioners taking greater responsibility for their antibiotic prescribing, increasing the role of caregivers as diagnosticians rather than medicine providers, improving their communication to patients about antibiotic treatment consequences, lessening the economic influences on prescribing, and identifying antibiotic alternatives. Abstract : Antibiotic Stewardship is a normalizing factor driven by risk‐benefit relationships, concerns about resistance and the microbiome, and guided by primum non nocere . Overuse factors include both the ideology of antibiotics as "cure‐alls" with minimal health costs, and the social, psychological, institutional, and economic factors that bias toward their inappropriate use.